Incidence and impact of violence and availability of support among Icelandic inmates - Kristel Dögg Vilhjálmsdóttir 1986- (2024)
Violence is a pervasive issue in prisons worldwide. Moreover, further research is needed on prison violence within the Icelandic prison system. This current study examined inmates' exposure to physical violence and sexual violence during incarceration, the effects of prison violence (e.g., anger, shame, depression, and anxiety), and the availability of support to those exposed to violence during incarceration. Participants were 209 inmates serving the remaining time of sentences at the halfway house Vernd. Age ranged from 18-66 years or older, and most participants were between the ages of 26 and 47. The participants' gender was excluded in the current study to keep the anonymity of minority groups in prisons in Iceland (e.g. females and people from the LGBTQ+ community). Answers from participants were collected from an ongoing survey at Vernd and were analyzed using descriptive statistics, multiple linear regression, and binomial logistic regression. The results showed that physical violence is a pervasive issue in Icelandic prisons, as well as sexual violence and sexual harassment. The results also showed that feelings of anger are the more apparent effect of prison violence, and the availability of support is inadequate and needs improvements. The current study highlights the prevalence of prison violence in Iceland, emphasizing the need for better support for inmates particularly those exposed to sexual violence. Keywords: Prison, inmates, violence, physical violence, sexual violence, incidence, incarceration, support. Ofbeldi er viðamikið vandamál í fangelsum út um allan heim. Þar að auki er þörf á rannsóknum á ofbeldi í fangelsum á Íslandi. Þessi rannsókn kannaði tíðni líkamlegs og kynferðislegs ofbeldis sem fangar upplifa í fangelsum á Íslandi, sem og afleiðingar slíks ofbeldis sem fangar upplifa í afplánun (t.d. reiði, skömm, þunglyndi og kvíða) og hvort það væri stuðningur til staðar fyrir fanga sem upplifa ofbeldi í afplánun. Þátttakendur voru 209 dómþolar sem voru að ljúka afplánun á áfangaheimilinu ...